Case Report: PAFAH1B1 Mutation and Posterior Band Heterotopia With Focal Temporal Lobe Epilepsy Treated by Responsive Neurostimulation - Gilliam, Frank G.; Ssentongo, Paddy; Sather, Michael; Kawasawa, Yuka I. (Frontiers in Neurology, 2021)
Subcortical band heterotopia (SBH), also known as double cortex syndrome, is a malformation of cortical development caused by inherited or somatic gene variants. We present a case of a young adult with posterior SBH and electroclinical features of focal neocortical temporal lobe epilepsy. Genomic blood analysis identified a pathogenic somatic mosaicism duplication variant of the PAFAH1B1 gene. Despite bilateral cortical MRI abnormalities, the interictal and ictal EEG findings indicated a focal epileptogenic region in the left posterior temporal region. Chronic responsive cortical neurostimulation across two four-contact depth electrodes placed 5 mm on either side of the maximal interictal spiking identified during intraoperative electrocorticography resulted in a consistent 28% reduction in duration of electrographic seizures and as well as constricted propagation. Although electrographic seizures continued, the family reported no clinical seizures and a marked improvement in resistant behaviors. This observation supports that focal neocortical neuromodulation can control clinical seizures of consistently localized origin despite genetic etiology, bilateral structural brain abnormalities, and continuation of non-propagating electrographic seizures. We propose that a secondary somatic mutation may be the cause of the focal neocortical temporal lobe epilepsy.